Functional improvement of injured retina following the adjuvant stem cell-based therapy. Preliminary report - Machalińska, Anna; Lubiński, Wojciech; Penkala, Krzysztof; Kawa, Miłosz; Baumert, Bartłomiej; Wiszniewska, Barbara; Karczewicz, Danuta; Machaliński, Bogusław (Klinika Oczna / Acta Ophthalmologica Polonica, 2011)
The purpose of this study was to appraise the functional response of damaged retina to the stem cell-based therapy in mice. The majority of disorders leading to the irreversible vision loss in the developed world is caused by retinal degeneration. Since, recent reports emphasized regenerative potential of bone marrow stem marrow stem/ progenitor cells (SPCs), we investigated here the beneficial effect of intravenously administrated SPCs on regeneration of acutely injured retina Material and methods: Selective chemical injury of murine retinas was induced by intravenous administration of sodium iodate (NaIO3) in its toxic dose. Flash electroretinogram (ERG), was performed in different time points after infusion of bone marrow-derived and negative for linage antigens population of SPCs. Results: Stem cell-based therapy resulted in gradual increase of b- wave amplitude in ERG recordings starting from the 3rd day after NaIO3 administration, what confirmed the improvement of retinal function in long-term observation. Conclusions: Our preliminary findings revealed that the selected stem cell-based therapy employed in the adjuvant mode has been shown to be effective in supporting the retinal function recovery after acute retinal damage.